Rational exuberance booms and asymmetric business cycles - Gene Ambrocio (Bank of Finland, 2015)
I propose a theory of information production and learning in credit markets in which the incentives to engage in activities that reveal information about aggregate fundamentals vary over the business cycle and may account for both the excessive optimism that fueled booms preceding financial crises and the slow recoveries that followed. In my theory, information about aggregate fundamentals is produced along two dimensions. First, optimistic beliefs lead to a fall in private investment in information reducing the quality of information available, an intensive margin. This gives rise to episodes of rational exuberance where optimism sustains booms even as fundamentals decline in the buildup to crises. Second, the quantity of information is increasing in the level of economic activity, an extensive margin. Thus, recoveries are slow since the low levels of investment and output provide little information about improvements in the state of the economy. Consistent with model predictions, I find supporting evidence in terms of a U-shaped pattern in macro-uncertainty measures over the business cycle. I also discuss the implications on endogenous information production on cyclical macro-prudential policy.
URN:NBN:fi:bof-201511261453
Keywords: D83; E32; E44; G01; G14; 330